Koncepcja systemu przedsiębiorstwa handlowego w łańcuchu dostaw - Odlanicka-Poczobutt, Monika (Conception of Trade Enterprise's System in Supply Chain, 2005)
Nowadays, the problems concerning logistics of distribution constitute an essential part of the economy. Trade enterprises, which transformed themselves from passive distributors to active participants in supply chain, offer their partners new solutions connected with organization of products and services flow and take part in creation of value for customer. The aim of this article is presentation of conception of trade enterprise's system in supply chain, for lack of precise discussions in accessible bibliography.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 253-262